Jump and sprint performance directly and 24 h after velocity- vs. failure-based training - Held, S.; Rappelt, L.; Deutsch, J.-P.; Donath, L. (International Journal of Sports Medicine, 2023)
The combination of plyometric and resistance training (RT) is frequently used to increase power-related adaptations. Since plyometric training is most effective when athletes are in a well-rested state, the acute effect of RT on plyometric performance should be carefully considered. Thus, 15 highly trained males (23.1±3.5 yrs, 1.80±0.06 m, 79.1±7.9 kg) completed a load- and volume-matched velocity-based RT session with 10% velocity loss (VL10) and traditional 1-repetition maximum-based RT session to failure (TRF) in a randomized order. Repeated sprints (5 × 15 m), countermovement jumps (CMJs), and drop jumps (DJs) were measured before, immediately after, and 24 h after both sessions. Lactate, heart rate, and perceived effort (RPE) were measured. Sprint, CMJ, and DJ revealed significant interaction effects (rANOVA p<0.001, ?p 2=0.63). Immediately afterward, sprint, DJ, and CMJ were less negatively affected (p=0.03, SMD=|0.40|) by VL10 vs. TRF. Sprint and CMJ were already recovered 24 h post-testing and showed no significant differences between TRF and VL10 (p=0.07, SMD=|0.21|). Twenty-four hours post-testing, DJs were still reduced during TRF but already recovered during VL10 (p=0.01, SMD=|0.70|). TRF resulted in higher lactate, heart rate, and RPE compared to VL10 (p=0.019, ? p 2=0.27, SMD=|0.68|). In conclusion, the non-failure-based VL10 impairs jump and sprint performance less than the failure-based TRF approach, despite matched volume and intensity.